FuZhengHuaYuJiangZhuTongLuoFang Prescription Modulates Gut Microbiota and Gut-Derived Metabolites in UUO Rats - Chen, Ziwei; Wu, Shaobo; Zeng, Yu; Chen, Zejun; Li, Xueying; Li, Jing; He, Long; Chen, Ming (Frontiers in Cellular and Infection Microbiology, 2022)
Background Alteration of intestinal flora and metabolites is closely related to chronic kidney disease (CKD) across early to advanced stages. FuZhengHuaYuJiangZhuTongLuoFang prescription (FZHY) is a Chinese herb that has been proven to effectively treat CKD, but the underlying mechanism is not clear. Methods Rats were subjected to intragastric treatment with FZHY 7, 14, and 21 days after unilateral ureteral obstruction (UUO) surgery, and kidney tissue, colon tissue, serum, and stool samples were collected. Results FZHY treatment effectively ameliorated UUO-induced renal function loss, renal injury and renal fibrosis, and colon tissue damage and fibrosis on day 7. The results of 16S flora analysis (day 7) showed that, compared with the UUO group, both the FZHY group and the sham group showed decreased levels of g_Monoglobus, g_Papillibacter, g_Eubacterium_nodatum, and g_Family_XIII_AD3011. Additionally, FZHY obviously induced the reduction of serum citrulline, glycoursodeoxycholic acid, 23-nordeoxycholic acid, 7-ketodeoxycholic acid, kahweol, lipoid B4, 4-(3,4-dihydro-2H-1,5-benzodioxepin-7-yl)-2-methyl-1,3-thiazole, taurolithocholic acid sodium salt, indoline-2-carboxylic acid, 5(S),15(S)-diHETE, and others and the increase of bilirubin, asparagine, and others, which were positively associated with the above four candidate bacteria. Moreover, FZHY increased the levels of ZO-1, occludin, and claudin-1 in the colonic mucosa and reduced the levels of CRP, TNF-α, IL-6, and IL-1 in the serum and LN, FN, Col-I, and Col-III in the tubulointerstitium of UUO rats on day 7. Conclusion Our study revealed that FZHY reduced kidney damage at the early stage of CKD by regulating the above four candidate bacteria biomarkers and gut-derived harmful metabolites, inhibiting the inflammation response and tubulointerstitial fibrosis, providing deep insight into CKD therapeutic strategy.